1993
DOI: 10.1002/jso.2930520409
|View full text |Cite
|
Sign up to set email alerts
|

Selective use of drains in thyroid surgery

Abstract: In the past, it was generally advised that every patient undergoing thyroid surgery have a drain placed because of the fear of post-operative hematoma. In the past 9 years, we have performed 400 thyroidectomies. For the first 6 years, we drained the operative site in most of thyroid procedures. However, it was apparent from our experience that drains had very little effect on the prevention of post-operative hematoma or of seroma. As a matter of fact, all four patients who required re-exploration in our initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 8 publications
(3 reference statements)
0
45
0
5
Order By: Relevance
“…Studies have shown that the average duration of drainage in uncomplicated head and neck operations is between 2-4 days. [7][8][9][10] The presence of drains may in fact encourage further drainage by stimulating tissue reactions or by creating a suction effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the average duration of drainage in uncomplicated head and neck operations is between 2-4 days. [7][8][9][10] The presence of drains may in fact encourage further drainage by stimulating tissue reactions or by creating a suction effect.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors have recommended the routine use of drainage after thyroidectomy to prevent hematoma and to detect bleeding early [17,18,19,20,21], this recommendation has been debated extensively in the literature [5,6,22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…In the past most surgeons employed wound drains routinely with the hope of decreasing the risk of acute airway obstruction by hematoma as well as postoperative hematoma or seroma [1][2][3][4][5]. Several authors, however, have suggested that use of drains could increase the risk of infection, the length of hospital stay, treatment costs, and discomfort for the patient.…”
Section: Introductionmentioning
confidence: 99%